Lightning in her hands - Vasquez Gilliland, Raquel (Berkley Romance, 2024)
"Gifted-or cursed-with the power to influence the weather, one woman must embrace her wild heart in the next electric romance from the author of Witch of Wild Things. Teal Flores is desperate for two things-control over her gift of weather, and a date to her ex's wedding. The first isn't possible until she finds her long-lost mother, but the second has a very handsome last-ditch solution: Carter Velasquez. Carter needs Teal too. His chance at receiving an inheritance is dependent on him being married by age thirty (blame his traditional Cuban grandmother), so who better to pose as his wife than Teal? But fake marriage and cohabitation prove tricky when mutual attraction charges the atmosphere-quite literally for Teal, whose volatile emotions cause lightning strikes. Together, Teal and Carter embark on a quest to find her mother and the answers she's searching for. But along the way, they'll discover something even better: a love that can weather any storm"--